Utilization of Sweat Potato Starch Wastewater and Monosodium Glutamate Wastewater for Cultivation of an Anti-Fungal Biocontrol Agent Paenibacillus Polymyxa - Bai, Zhihui; Gu, Likun; Su, Yanming; Jin, Bo; Zhuang, Guoqiang (IntechOpen, 2010)
None